The transCampus Metabolic Training Programme Explores the Link of SARS-CoV-2 Virus to Metabolic Disease - Bornstein, S. R.; Guan, K.; Brunßen, C.; Mueller, G.; Kamvissi-Lorenz, V.; Lechler, R.; Trembath, R.; Mayr, M.; Poston, L.; Sancho, R.; IRTG Study Group; Ahmed, S.; Alfar, E.; Aljani, B.; Alves, T. C.; Amiel, S.; Andoniadou, C. L.; Bandral, M.; Belavgeni, A.; Berger, I.; Birkenfeld, A.; Bonifacio, E.; Chavakis, T.; Chawla, P.; Choudhary, P.; Cujba, A. M.; Delgadillo Silva, L. F.; Demcollari, T.; Drotar, D. M.; Duin, S.; El-Agroudy, N. N.; El-Armouche, A.; Eugster, A.; Gado, M.; Gavalas, A.; Gelinsky, M.; Guirgus, M.; Hansen, S.; Hanton, E.; Hasse, M.; Henneicke, H.; Heller, C.; Hempel, H.; Hogstrand, C.; Hopkins, D.; Jarc, L.; Jones, P. M.; Kamel, M.; Kämmerer, S.; King, A. J. F.; Kurzbach, A.; Lambert, C.; Latunde-Dada, Y.; Lieberam, I.; Liers, J.; Li, J. W.; Linkermann, A.; Locke, S.; Ludwig, B.; Manea, T.; Maremonti, F.; Marinicova, Z.; McGowan, B. M.; Mickunas, M.; Mingrone, G.; Mohanraj, K.; Morawietz, H.; Ninov, N.; Peakman, M.; Persaud, S. J.; Pietzsch, J.; Cachorro, E.; Pullen, T. J.; Pyrina, I.; Rubino, F.; Santambrogio, A.; Schepp, F.; Schlinkert, P.; Scriba, L. D.; Siow, R.; Solimena, M.; Spagnoli, F. M.; Speier, S.; Stavridou, A.; Steenblock, C.; Strano, A.; Taylor, P.; Tiepner, A.; Tonnus, W.; Tree, T.; Watt, F.; Werdermann, M.; Wilson, M.; Yusuf, N.; Ziegler, C. G. (Hormone and Metabolic Research, 2021)
Currently, we are experiencing a true pandemic of a communicable disease by the virus SARS-CoV-2 holding the whole world firmly in its grasp. Amazingly and unfortunately, this virus uses a metabolic and endocrine pathway via ACE2 to enter our cells causing damage and disease. Our international research training programme funded by the German Research Foundation has a clear mission to train the best students wherever they may come from to learn to tackle the enormous challenges of diabetes and its complications for our society. A modern training programme in diabetes and metabolism does not only involve a thorough understanding of classical physiology, biology and clinical diabetology but has to bring together an interdisciplinary team. With the arrival of the coronavirus pandemic, this prestigious and unique metabolic training programme is facing new challenges but also new opportunities. The consortium of the training programme has recognized early on the need for a guidance and for practical recommendations to cope with the COVID-19 pandemic for the community of patients with metabolic disease, obesity and diabetes. This involves the optimal management from surgical obesity programmes to medications and insulin replacement. We also established a global registry analyzing the dimension and role of metabolic disease including new onset diabetes potentially triggered by the virus. We have involved experts of infectious disease and virology to our faculty with this metabolic training programme to offer the full breadth and scope of expertise needed to meet these scientific challenges. We have all learned that this pandemic does not respect or heed any national borders and that we have to work together as a global community. We believe that this transCampus metabolic training programme provides a prime example how an international team of established experts in the field of metabolism can work together with students from all over the world to address a new pandemic.
Keywords: COVID-19; transCampus; metabolic training programme